1998
DOI: 10.1111/j.1151-2916.1998.tb02665.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Mechanism of Nonstoichiometric 1:1 Short‐Range Ordering in NiO‐Doped Pb(Mg1/3Nb2/3)O3 Relaxor Ferroelectrics

Abstract: A new mechanism of the nonstoichiometric, 1:1 short-range ordering, which leads to enhanced diffuse phase transition (DPT), was proposed and tested using NiO-doped Pb(Mg 1/3 Nb 2/3 )O 3 as a model system for Pb(B 1/3 B؆ 2/3 )O 3 -type relaxor ferroelectrics. The enhanced DPT and the increase in the intensity of {h+ 1 ⁄2,k+ 1 ⁄2,l+ 1 ⁄2}-type superlattice reflection both were observed in the presence of NiO. These observations were interpreted as the increase in the number density of the short-range-ordered nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 30 publications
(65 reference statements)
0
2
0
2
Order By: Relevance
“…The bulk electrical resistivity for a given semicircle was obtained from the intercept of the semicircle with the Z′‐axis, and the corresponding dielectric permittivity was estimated from the peak of the semicircle. In comparison of dielectric permittivity estimated from the complex impedance spectrum with that from the temperature‐dependent dielectric permittivity spectrum, it is confirmed that the semicircle was caused by a conducting mechanism mainly related to the bulk perovskite grains . According to the calculation results based on impedance data, it is found that the doping of Fe, Co, and Ni ions leads to the decrease of electrical resistivity, which can be attributed to the generation of positively charged carriers.…”
Section: Resultsmentioning
confidence: 74%
“…The bulk electrical resistivity for a given semicircle was obtained from the intercept of the semicircle with the Z′‐axis, and the corresponding dielectric permittivity was estimated from the peak of the semicircle. In comparison of dielectric permittivity estimated from the complex impedance spectrum with that from the temperature‐dependent dielectric permittivity spectrum, it is confirmed that the semicircle was caused by a conducting mechanism mainly related to the bulk perovskite grains . According to the calculation results based on impedance data, it is found that the doping of Fe, Co, and Ni ions leads to the decrease of electrical resistivity, which can be attributed to the generation of positively charged carriers.…”
Section: Resultsmentioning
confidence: 74%
“…Tungsten bronze (TB) structure based polar dielectrics form a very important class of non-toxic materials offering competent structural, electrical, optical, photocatalytic and electrocaloric response compared to corresponding toxic perovskite oxides like lead magnesium niobate (PMN), lead zirconium niobate (PZN), lead zirconium titanate (PZT), lanthanum-modified lead zirconate titanate (PLZT), lead scandium niobate (PSN) etc [1][2][3] . Many TB structures offer variety of applications emerging from NbO6 octahedral distortions and phase transition between different polymorphs.…”
Section: Introductionmentioning
confidence: 99%
“…Esta y otras características son las que hacen que este conjunto de materiales sean clasificados como Relaxores (RE). Este es el caso del PMN (PbMg 1/3 Nb 2/3 O 3 ), cuya TFD es función del ordenamiento químico a corta distancia de las especies del sitio B (Mg +2 y Nb +5 ) en la estructura perovskita A(B',B'')O 3 [1,2].…”
Section: Introductionunclassified
“…Esta y otras características son las que hacen que este conjunto de materiales sean clasificados como Relaxores (RE). Este es el caso del PMN (PbMg 1/3 Nb 2/3 O 3 ), cuya TFD es función del ordenamiento químico a corta distancia de las especies del sitio B (Mg +2 y Nb +5 ) en la estructura perovskita A(B',B'')O 3 [1,2].En este tipo de estructura perovskita, el comportamiento RE se puede generar a través de dos tipos de distorsiones: electrostática y mecánica. Mientras la distorsión mecánica proviene de las diferencias de radios iónicos de los cationes B y causa la distorsión de la red del cristal directamente, la distorsión de origen electrostática es generada por un desequilibrio de cargas en la red del cristal, debido a la existencia de micro-regiones ricas en niobio.…”
unclassified